RM129 thousand for Ramadhan Activities - Nur Laila, Afandi (2018)
Pekan, 16 May – Islamic Centre & Human Development (PIMPIN) will be organizing Ramadhan Festival to enliven the Holy Month of Ramadhan. Various activities will done from 15 May to 13 June 2018, such as Tarawikh Prayer, Quran Recital, Iftar Jamaie, Nuzul Al-Quran Seminar and many more.